Trading Platform Powered by Blockchain (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Blockchain, the distributed ledger System advances in emerging decentralized systems that simplify paper processes and disrupt long-settled business models [1]. In Blockchain, data are encrypted, documented, dealing blocks together with timestamps are joined along to create an extensive, deep-seated record. Blockchain is a distributed ledger technology that aims to ensure transparency, integrity, and data security so that it cannot tamper. Blockchain technology is best notable for its association with cryptocurrency Bitcoin. It will have enormous applications in government, finance trade, accounting, and Business method Management. Therefore, an attempt is made to investigate its scope within the trading Sector by the decentralized and distributed ledger technology in this study. This paper examines the further improvement of trade finance utilizing blockchain technology.